Equivalent grid-following inverter-based generator model for ATP/ATPDraw fast time-domain simulations - Luchini, Matheus Bassani (2023)
Due to the increasing penetration of inverter-based resources (IBR) in modern power grids, most phasor-domain models became insufficient to represent the system dynamics during steady-state and fault conditions. As a result, IBR time-domain models gained importance. However, complete models that include switching elements and their respective controllers are usually time-consuming and difficult to initialize, especially in systems with several IBRs connected. Thus, this work presents an equivalent time-domain gridfollowing inverter-based generator (IBG) model, which can be used in Electromagnetic Transients Programs (EMTP). The proposed IBG model is developed in the Alternative Transients Program (ATP) using the ATPDraw graphical interface. A complete benchmark photovoltaic model available in ATP/ATPDraw environment is taken as reference to evaluate the proposed equivalent IBG model under steady-state and fault scenarios. The obtained results showed that the proposed model is simpler and less time-consuming than the complete model, being capable of easily considering the implementation of different components/controls of IBR in EMTP. The settings used in the implemented control schemes proved to be effective, resulting in an average error of about 2.21% during fault conditions. Also, a reduction of about 70 % in the execution time was achieved when compared to the analyzed benchmark one, attesting its usefulness for power system studies with high presence of grid-following IBRs.